Incidence Of Clostridium difficile Infection And Associated Risk Factors Among Hospitalized Children In Qatar - Khalil A; Hendaus MA; Elmagboul E; Mohamed A; Deshmukh A; Elmasoudi A (Dove Medical Press, 2019)
Ahmed Khalil,1 Mohamed A Hendaus,2 Emad Elmagboul,3 Asmaa Mohamed,1 Anand Deshmukh,3 Ahmed Elmasoudi1 1Department of Pharmacy, Hamad General Hospital, Doha, Qatar; 2Department of Pediatrics, Hamad Medical Corporation, Sidra Medicine, Weill Cornell Medicine, Doha, Qatar; 3Microbiology Laboratory, Hamad General Hospital, Doha, QatarCorrespondence: Ahmed KhalilHamad General Hospital (HGH), Hamad Medical Corporation (HMC), Doha 3050, QatarTel +974 55078679Email akhalil7@hamad.qaBackground: Clostridium difficile infection (CDI) is the single most common cause of nosocomial diarrhea in both adults and children. There is a deficiency in the literature regarding the incidence and associated risk factors in hospitalized children. This study aimed to determine the incidence of CDI and its associated risk factors.Methods: A retrospective study was conducted among 200 pediatric patients admitted to the pediatric ward at Hamad General Hospital (HGH) in Qatar. The study collected data from January 1, 2015 till December 2015. Univariate and multivariate logistic regression methods were used to assess each risk factor of CDI.Results: Among the 200 patients, 23 were diagnosed with CDI (incidence: 5.9 per 1000 inpatient admission cases). The mean patient age (±SD) was 6.4 ± 3.4 years. The incidence of antibiotic exposure (22.5; 95% CI: 15.0–38.7; P <0.001), prolonged hospitalization (28.9; 95% CI: 17.1–43.3; P <0.001), and enteral feeding (33.3; 95% CI: 15.9–55.1; P <0.001) were significant risk factors for CDI.Conclusion: Antibiotics exposure, prolonged hospitalization, and enteral feeding were significant risk factors of CDI in hospitalized children; thus, emphasizing the importance of antimicrobial stewardship programs in the prevention of hospital-associated infection. Further prospective studies are needed to assess the trend in incidence and to identify other risk factors of CDI.Keywords: antimicrobial stewardship, Clostridium difficile infection (CDI), hospital acquired, hospitalized pediatric patients, risk factors